Studi Kehilangan Air Fisik dan Kehilangan Air Komersial (Studi Kasus: PDAM Kota Malang) - Anwar Romdloni; Agus Ahyar; Eddy S Soedjono (CV. Ridwan Publisher, 2021)
PDAM is responsible for providing drinking water services to the community. Physical and commercial water loss results in inability to meet drinking water needs, declining revenues, increased operating costs, and deteriorating infrastructure. One of the efforts made by PDAM Malang City to deal with the consequences of physical and commercial water loss is to conduct a water loss control program. Water loss is defined as the difference between production and water bills based on the consumer meter. Analyze this research data by identifying the problem and then the efforts made to overcome it. Identification begins with identifying the overall region through an existing network map and identification through a water balance. The rate of water loss obtained from the water balance in february 2021 is physical water loss of 16,60% and commercial water loss of 3.16% with a total water loss of 19,76% equivalent to 813.522 m3 per month with a loss of Rp. 3.283.138.900, - per month